ANALISIS BIBLIOMETRIK TENTANG KETERKAITAN KETAHANAN AIR, ENERGI, DAN PANGAN - Purwanto, Aries; Nurisamunandar, Agustien (CREATIVE RESEARCH JOURNAL, 2021)
This literature trend analysis focused on the water, energy, and food (WEF) security nexus-related topics that are increasingly discussed in global society, academia, business, and policy. The objective of this study is to examine the trends of scientific publications in this issue using the Scopus Database and Google Scholar during the period of year 2000 to 2019. It was conducted by employing six searching phrases with three selected categories i.e. year of publication, subject area, and type of documents in Scopus search engine (SCO) and one category of year of publication in Google Scholar (GOS). The results indicate the increasing number of research document over time on WEF security topic either in the separated three sectors or in the integration of them in the perspective of nexus. Additionally, the use of different searching phrases which represent both sectoral and integrated approach indicates the perspective changes of scientific community in observing water, energy and food resources. Furthermore, interconnectedness between WEF system and other exogenous factors such as climate, population, forest, industry, and other economic developments have been revealed through the existing studies. All the findings are expected to bring a better insight for the researcher in conducting research on this topic and broaden the scope instead of only WEF system without considering other exogenous factors. Further study on the applicability of the nexus concepts in any level including local context is needed to prove that this concept is not only ‘on paper’ but also can be well[1]implemented to assist policy-makers in managing WEF resources